Féminismes et luttes contre l'homophobie: de l'apprentissage à la subversion des codes - Bard, Christine; Bastien Charlebois, Janik; Boisclair, Isabelle; Bourque, Dominique; Charbonneau, Amélie; Deshoulières, Étienne; Horincq Detournay, Rosine; Laprade, Bruno; Lebreton, Christelle; Maiorano, Sabrina; Ricard, Nathalie; Vallerand, Olivier (Les cahiers de l'IREF. Collection Agora, 2016)
En 1903, à Berlin, Anna Rueling appelait le mouvement homosexuel et le mouvement des femmes à s’entraider puisque tous deux luttaient pour la liberté et l’autodétermination individuelle. Plus d’un siècle plus tard, quelles convergences peut-on observer entre féminismes et luttes contre l’homophobie? Sur le plan de la pensée, quels rapprochements contemporains peut-on établir entre le champ des études féministes et celui de la diversité sexuelle et de genre? Comment s’articule l’intersection entre ces deux systèmes de différenciation hiérarchique que sont le sexisme et l’hétérosexisme ? Quels théories et concepts y circulent de manière transversale, et avec quelles redéfinitions? Ces questions ont guidé l’organisation du colloque «Féminismes et luttes contre l’homophobie: zones de convergence» tenu dans le cadre du congrès de l’ACFAS 2014 à l’Université Concordia, Montréal, le 16 mai 2014.
Keywords: amériques; approches et analyses; corps; cours; discipline; droit; empowerment; europe; france; homophobie; lesbianisme; pol5185; politique; pornographie; premier cycle; queer; québec; régions géographiques; science politique; science politique et droit; sciences humaines; sexualité; sociologie; thématiques; violences; violences contre les femmes*; violences sexistes et sexuelles

A messy trajectory: From medical sociology to crip theory - Egner J. (Research in Social Science and Disability ; 9, 2016)
Purpose The purpose of this paper is to draw attention to the work of sociologists who laid the foundation for queer and crip approaches to disability and to address how queer and crip theory has and can help to re-conceptualize our understandings of health, illness, disability, and sexuality. Methodology/approach This paper is an examination of historical moments and prominent literature within medical sociology and sociology of disability. Sociological and popular understandings of disability and sexuality have often mirrored each other historically. Although this literature review focuses primarily on medical sociology and disability studies literature, some works of scholars specializing in gender studies, sexuality, literature, history, and queer studies are also included Findings In this paper, I argue that the medicalization and pathologization of human differences specifically as it pertains to sexuality and disability within the medical sociological literature have led to constructionist, social model, and feminist critiques. It is these critiques that then laid the foundation for the development of queer and crip theoretical approaches to both disability and sexuality. Originality/value Crip and queer approaches to disability provide a clear call for future sociological research. Few social science scholars have applied queer and crip approaches in empirical studies on disability. The majority of work in this area is located in the humanities and concerned with literary criticism. A broader array of empirical work on the intersection of sexuality and disability from queer/crip perspectives is needed both to refine these postmodern theoretical models and to examine their implications for the complex lived experience that lies at the intersection of sexuality and disability. In queering disability and cripping sexuality and gender, we may be able not only to more fully conceptualize disability, sexuality, and gender as individual social categories, but also to more fully understand the complex intersection of these social locations.
Keywords: EDI; approches et analyses; care; cours; crip; discipline; histoire et politique; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sociologie; sofia; thématiques

Feminism is queer: the intimate connection between queer and feminist theory - Marinucci, Mimi (Zed Books, 2016)
Feminism is Queer is an introduction to the intimately related disciplines of gender and queer theory. While guiding the reader through complex theory, the author develops the original position of "queer feminism, " which presents queer theory as continuous with feminist theory. While there have been significant conceptual tensions between second wave feminism and traditional lesbian and gay studies, queer theory offers a paradigm for understanding gender, sex, and sexuality that avoids the conflict in order to develop solidarity among those interested in feminist theory and those interested in lesbian and gay rights. This accessible and comprehensive textbook carefully explains nuanced theoretical terminology and includes extensive suggested further reading to provide the reader with a full andthorough understanding of both disciplines.--Publisher information.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; militance; philosophie; premier cycle; queer; sciences humaines; soc2014; thématiques

Lesbian camp: An unearthing - Nielsen, Elly-Jean (Journal of Lesbian Studies, 2016)
Camp—a sensibility, a style, and a form of artistic selfexpression—is an elusive concept said to be in the eye of the beholder. To refute Susan Sontag’s (1966) claims that camp is apolitical and not especially homosexual, a number of recent scholarly works have been geared toward revealing camp’s fundamental gayness. With the odd footnote aside, lesbian camp has been collapsed into the category of gay male camp, if not eclipsed entirely. Despite the negligible efforts made to legitimize lesbian camp, there are numerous salient cultural examples one might draw on to illustrate, typify, and substantiate a lesbian camp sensibility. I lay the ground work for this scholarly exercise by outlining various definitions and critiques of camp, and by discussing its history and application to queer theory. Then, to unveil lesbian camp, three nonmutually exclusive categories are discussed: classic, erotic, and radical. By gathering various strands of inquiry, and various textual examples (e.g., photography, artistic performances, and literary tropes), this article attempts to reach a more inclusive and nuanced understanding of lesbian camp.
Keywords: approches et analyses; butch/femme; discipline; personnes lesbiennes; psychologie; queer; ressource en ligne; sciences humaines

Se retrouver entre soi pour se reconnaitre: conceptions du genre et regulation des echanges dans un forum de personnes trans - Pastinelli, Madeleine; Dery, Caroline (Anthropologie et Societes, 2016)
Les possibilités de communication anonyme permises par les nouvelles technologies amènent des personnes qui ont en commun des pratiques ou des expériences qui les stigmatisent à se retrouver à l’abri des regards pour échanger entre elles et former des communautés en ligne. Ce faisant, elles se réapproprient leur expérience dans un langage choisi qui leur permet de redonner sens à des identités et des pratiques marginales ou considérées comme déviantes ou pensées comme relevant de la pathologie par le discours médical. L’enquête que nous avons menée dans une communauté en ligne de personnes trans éclaire la manière dont la fréquentation de celle-ci permet à ces personnes de se (re)connaître dans leur expérience particulière du corps et du genre et de faire sens de cette expérience. La volonté communément partagée par ces personnes de penser autrement leur expérience donne lieu à la rencontre d’une multitude de conceptions différentes, et parfois incompatibles entre elles, de l’identité de genre et de l’expérience trans. L’analyse se penche plus particulièrement sur la régulation du discours et des échanges qui est faite par les modérateurs dans ce contexte et sur le type de consensus qu’elle rend possible.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; outils; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; transféminisme

True loves, dark nights: Queer performativity and grieving through music in the work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)
This dissertation studies the cultural significance of Canadian-American singer/songwriter Rufus Wainwright's (b. 1973) album All Days Are Nights: Songs for Lulu (Decca, 2010). Lulu was written, recorded, and toured in the years surrounding the illness and eventual death of his mother, beloved Quebecoise singer/songwriter Kate McGarrigle. The album, performed as a classical song cycle, stands out amongst Wainwright's musical catalogue as a hybrid composition that mixes classical and popular musical forms and styles. More than merely a collection of songs about death, loss, and personal suffering, Lulu is a vehicle that enabled him to grieve through music. I argue that Wainwright's performativity, as well as the music itself, can be understood as queer, or as that which transgresses traditional or expected boundaries. In this sense, Wainwright's artistic identity and musical trajectory resemble a rhizome, extending in multiple directions and continually expanding to create new paths and outcomes. Instances of queerness reveal themselves in the genre hybridity of the Lulu song cycle, the emotional vulnerability of Wainwright's vocal performance, the deconstruction of gender norms in live performance, and the circulation of affect within the performance space. In this study, I examine the song cycle form, Wainwright's musical score and vocal performance, live performance videos, and fan reactions to live performances in order to identify meaningful moments where Wainwright's musical and performative decisions queer audience expectations. While these musical moments contribute to the already rich and varied lineage of the gay male artist in both classical and popular music, I argue that Wainwright's queer performativity and nontraditional musical choices speak to larger issues important to American culture in the contemporary moment. These issues include the visibility of male public mourning and the healing power of artistic expression in the face of traumatic loss.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; culture populaire; deuil; discipline; genre; mémoires/thèses; philosophie; périodes historiques; queer; ressource en ligne; résistance; sciences humaines; émotions